2012
DOI: 10.1007/s00148-012-0438-4
|View full text |Cite
|
Sign up to set email alerts
|

The psychic costs of migration: evidence from Irish return migrants

Abstract: Within the economics literature, the 'psychic costs' of migration have been incorporated into theoretical models since Sjaastad (J Polit Econ 70:80-93, 1962). However, the existence of such costs has rarely been investigated in empirical papers. In this paper, we look at the psychic costs of migration by using alcohol problems as an indicator. Rather than comparing immigrants and natives, we look at the native-born in a single country and compare those who have lived away for a period of their lives and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
(27 reference statements)
2
28
0
Order By: Relevance
“…We found that mental ill-health is associated with decreased attendance at religious services and is a significant feature of the lives of male return migrants (who spent longer than 10 years away), a possible indicator of readjustment disaffection with religion. Social loneliness and isolation-dominating features of the fully adjusted models-are consistent with qualitative research on the experiences of returning migrants (Barrett & Mosca, 2013;Ryan, Jorm, Toumbourou, & Lubman, 2015). Although longerterm male return migrants are more likely to report mental ill-health we note that this effect disappears in the fully adjusted model.…”
Section: Determinants Of Mental Ill-healthsupporting
confidence: 80%
“…We found that mental ill-health is associated with decreased attendance at religious services and is a significant feature of the lives of male return migrants (who spent longer than 10 years away), a possible indicator of readjustment disaffection with religion. Social loneliness and isolation-dominating features of the fully adjusted models-are consistent with qualitative research on the experiences of returning migrants (Barrett & Mosca, 2013;Ryan, Jorm, Toumbourou, & Lubman, 2015). Although longerterm male return migrants are more likely to report mental ill-health we note that this effect disappears in the fully adjusted model.…”
Section: Determinants Of Mental Ill-healthsupporting
confidence: 80%
“…The study by Barrett and Mosca [43] indicates that non-pecuniary elements, such as psychological costs like the emotional impact of leaving familiar neighborhood, also have an unfavorable influence on housing adjustment, suggesting that our simulations are insufficient with respect to the major barriers of transaction costs. Further research should investigate tenants' exit behaviors from both the subjective and objective barriers.…”
Section: Discussionmentioning
confidence: 94%
“…Such psychological costs for migrants are incorporated into theoretical models in the economics literature (Sjaastad, 1962). Recently, Barrett and Mosca (2013) empirically measured psychological costs using individual-level data. They found that those who lived away from their home areas were more likely to suffer from alcohol problems than those who stayed in them.…”
Section: Hypothesesmentioning
confidence: 99%